Attitudes of Muslim Americans toward Homosexuality and Marriage Equality: Moving Beyond Simply Understanding Christian Public Opinions. Issue 4 (22nd October 2019) - Bratton, Tabrina M.; Lytle, Robert; Bensel, Tusty ten
Abstract : A number of studies have found a relationship between religious affiliation and attitudes toward LGBQ individuals. To date, however, research on religious attitudes has focused primarily on Christians. We expanded upon existing research by including two of the three largest U.S. religions previously overlooked—Islam and Judaism. We used data from the 2014 Religious Landscape Study, which provided a larger sample of Jewish ( n  =   475) and Muslim ( n  =   135) respondents than most public opinion surveys. We found that Muslim and Protestant participants were the least accepting of homosexuality and supportive of same‐sex marriage compared with Roman Catholic and Jewish participants. Results also showed that fundamentalism and religiosity were significant predictors of attitudes toward homosexuality and same‐sex marriage across all participants, regardless of denomination. Implications for future research and data collection efforts learned from this study are discussed.